Total Chemical Synthesis of SUMO and SUMO‐Based Probes for Profiling the Activity of SUMO‐Specific Proteases. Issue 29 (14th June 2018) - Mulder, Monique P. C.; Merkx, Remco; Witting, Katharina F.; Hameed, Dharjath S.; El Atmioui, Dris; Lelieveld, Lindsey; Liebelt, Frauke; Neefjes, Jacques; Berlin, Ilana; Vertegaal, Alfred C. O.; Ovaa, Huib
Abstract: SUMO is a post‐translational modifier critical for cell cycle progression and genome stability that plays a role in tumorigenesis, thus rendering SUMO‐specific enzymes potential pharmacological targets. However, the systematic generation of tools for the activity profiling of SUMO‐specific enzymes has proven challenging. We developed a diversifiable synthetic platform for SUMO‐based probes by using a direct linear synthesis method, which permits N‐ and C‐terminal labelling to incorporate dyes and reactive warheads, respectively. In this manner, activity‐based probes (ABPs) for SUMO‐1, SUMO‐2, and SUMO‐3‐specific proteases were generated and validated in cells using gel‐based assays and confocal microscopy. We further expanded our toolbox with the synthesis of a K11‐linked diSUMO‐2 probe to study the proteolytic cleavage of SUMO chains. Together, these ABPs demonstrate the versatility and specificity of our synthetic SUMO platform for in vitro and in vivo characterization of the SUMO protease family. Abstract : A direct linear synthesis was developed for SUMO proteins, which enables the synthesis of SUMO‐derived activity‐based probes, including a novel diSUMO probe. These reagents hold great potential for studying the specificity of SUMO‐specific proteases, as demonstrated in vitro and in cells. The facile synthesis strategy presented here enables the generation of a diversifiable SUMO toolbox, thereby opening novel avenues for research and drug discovery.